The impact of CO2-driven ocean acidification on early development and calcification in the sea urchin Strongylocentrotus intermedius. Issue 1 (15th November 2016) - Zhan, Yaoyao; Hu, Wanbin; Zhang, Weijie; Liu, Minbo; Duan, Lizhu; Huang, Xianya; Chang, Yaqing; Li, Cong
Abstract: The impact of CO2 -driven ocean acidification(OA) on early development and calcification in the sea urchin Strongylocentrotus intermedius cultured in northern Yellow Sea was investigated by comparing fertilization success, early cleavage rate, hatching rate of blastulae, larvae survival rate at 70 h post-fertilization, larval morphology and calcification under present natural seawater condition (pH = 8.00 ± 0.03) and three laboratory-controlled acidified conditions (OA1, △pH = − 0.3 units; OA2, △pH = − 0.4 units; OA3, △pH = − 0.5 units) projected by IPCC for 2100. Results showed that pH decline had no effect on the overall fertilization, however, with decreased pH, delayed early embryonic cleavage, reduced hatching rate of blastulae and four-armed larvae survival rate at 70 h post-fertilization, impaired larval symmetry, shortened larval spicules, and corrosion spicule structure were observed in all OA-treated groups as compared to control, which indicated that CO2 -driven OA affected early development and calcification in S. intermedius negatively. Highlights: Overall process of fertilization was not affected by CO2 -driven OA in S. intermedius . A dose-dependent decline in both the percent hatched blastulae and four-armed larvae survival rate at 70 h post-fertilization were observed as compared to those of control in general. The proportions of asymmetric larvae with different asymmetry degree increased with decreasing pH in all OA-treatments as compared to that of the control, moreover, the trend of larval asymmetry degree was linearly increase as pH decreased. Spicules with corroded calcified surface structure of were observed in all OA-treatments in a dose-dependent manner with decreased pH.